Investigasi Keberadaan dan Arah dari Pipa Bawah Tanah dengan Metode Kelistrikan - Mahmudi, Agus; Kuspijani, Kuspijani (Universitas Trunojoyo Madura, 2008)
The research to investigate existence and direction of underground pipe has been done. Thepipe has 10 cm deep on the sand, and it determines the potential distribution by using 10 cm grid on 140 x 280 cm size ·of grid. Finally, existence and direction of underground pipe was identified that indicated with highest potential anomaly between surrounding.